On the Solution of a Nonlinear Semidefinite Program Arising in Discrete-Time Feedback Control Design - El-Sayed M. E. Mostafa (Journal of Applied Mathematics)
A sequential quadratic programming method with line search is analyzed and studied for finding the local solution of a nonlinear semidefinite programming problem resulting from the discrete-time output feedback problem. The method requires an initial feasible point with respect to two positive definite constraints. By parameterizing the optimization problem we ease that requirement. The method is tested numerically on several test problems chosen from the benchmark collection (Leibfritz, 2004).